EFFECTS OF MINCED TILAPIA AND PORK LEVELS ON THE SENSORY QUALITY AND ACCEPTABILITY OF FISH PORK CHORIZO - Ramirez, Ronald M (Journal of Agriculture and Technology Management, 2022)
Tilapia is locally farmed and abundantly found in Camotes islands specifically in Lake Danao, San Francisco, Cebu. Enhancing its taste and processing is part of value addition to the tilapia commodity. The study aimed to determine the organoleptic properties for fish pork chorizo formulated from minced tilapia with different levels of pork. The experimental design was laid out in the study using Complete Randomized Design (CRD). There were four treatments prepared in three replications that varied in the percentage of pork and tilapia meat. A control variable of using pure pork chorizo is used. Results revealed that pure pork chorizo (control) is very much favored by the sensory panelists but with the formulation of 20% tilapia and 80% of pork for fish pork chorizo is liked moderately by the panelists and generated highest rating of all the mixtures or treatments. Analysis of variance (ANOVA) showed no significant mean differences at 5% percent level significance among treatments in all of the sensory attributes except flavor and texture with significant values. Thus, varying amounts of tilapia and pork altered its flavor and texture. Formulation of 20% tilapia and 80% pork is recommended for fish pork chorizo.